Sistem Pendukung Keputusan Penentuan Siswa Berprestasi Dengan Menggunakan AHP (Studi Kasus : SMA Negeri 1 Bandar Lampung) - Ramandhita Herdianto; Yuli Syafitri; Yodhi Yuniarthe (Jurnal Teknologi dan Informatika (JEDA), 2022)
SMAN 1 Bandar Lampung is one of the senior high schools located on Jl. Gen. Sudirman No.41, Rw. Sea, District. Tj. Karang Tim., Bandar Lampung City. The process that has been running so far in determining the outstanding students of SMAN 1 Bandar Lampung is by looking at the daily grades at school given by the teacher. where it is deemed less effective because there is a high possibility of errors in the calculation process in determining outstanding students, to assist the school in determining outstanding students, a system is needed to support decisions using the Analytical Hierarchy Process (AHP) method in determining outstanding students so that the decision results become more effective and efficient. The purpose of the research is to create and implement a decision support system that can assist in identifying students who excel as well as build a system that determines students who excel. While the benefit of this research is a decision support system based on AHP is anticipated to make it easier to identify outstanding students.